Regenerative Medicine with Recombinant Human Granulocyte Colony Stimulating Factor: Insights and Applications - Abdul-Hameed, Hala Adnan; Saloom, Hayder Fadhil; Jany, Saleh Johy (AL-Kindy College Medical Journal, 2025)
Regenerative medicine is an interdisciplinary approach that introduces treatment modalities that mimic natural biological mechanisms. These treatment modalities include growth factors, cytokines modulation of the signaling cascade, and customized tissue engineering therapies with the least invasive methods. Granulocyte colony-stimulating factor (G-CSF) is a hematopoietic cytokine that enhances granulocyte lineage cell proliferation, differentiation, and activation. Evidence-based studies have analyzed the effect of using recombinant human rh G-CSF on stem cell and progenitor cell recruitment and tissue repair and regeneration via anabolic protein upregulation and antiapoptotic mechanism enhancement. Promising regenerative effects of rh G-CSF administration have been reported in medical fields, such as providing long-term effects of neuroprotection in Parkinson’s, Huntington’s, and Alzheimer’s diseases, ischemic disease, wound healing, diabetic foot repair, cardiovascular disease, reproductive biology, liver disease, and osteoid tissue regeneration.